Travel budget recommendation system by using rule-based filtering / Nor Anis Arina Zafie - Zafie, Nor Anis Arina (2020)
The objective of this paper is to discuss the travel budget recommendation system develops in the web-based application. This system is developed to simplify searching and explore process using the rule-based technique. Users always have a hard time in comparing the places and activities that they want to try and visit. This project aimed is to make it convenience to user when it comes to recommend the places and activities that fit perfectly with users’ preferences. The technique rule-based is used in this system where it helps to filter the destination, activity and budget that meet the users’ preferences. User will find it convenience when they just need to enter the destination, activity and budget of their preferences and the system will recommend list of places and activities that is most likely like what they want. In order to achieve the objectives of the project, the suitable research methodology are being applied as a guideline through this research is waterfall model. There are six main phases of activities in this project, which is requirements analysis, system design, implementation, testing, deployment and lastly maintenance. Based on the finding, the system is accurate and valid where the result was met the expectations. This system also consists of limitation and recommendation for future to make the system more efficient. The future work include to make the system be able to accept the booking and user can directly buy the tickets from it instead of only recommend the places.